Optimization of Coconut and Empowerment of Suka Maju Women Farmers Group in Namangkewa Village - Nasa, Rikardus; Sada, Mariana; Chotimah, Nur (Jurnal Abmas Negeri (JAGRI), 2025)
The utilization of coconut in Namangkewa Village was previously limited to personal consumption, despite the fact that the village possessed significant potential that had not yet been optimized to enhance its economic value. The objective of this community service initiative was to empower KWT Suka Maju through comprehensive training in coconut fruit processing. The training approach encompassed socialization, practical training, implementation, and subsequent evaluation. Results from this initiative revealed a marked improvement in participants' skills in transforming coconuts into high-value products. Processed products such as Virgin Coconut Oil demonstrated strong potential to substantially boost the household income of KWT members. The program also fostered greater awareness among participants regarding the importance of leveraging local resources to strengthen the village's economic stability. Despite challenges related to access to production equipment and marketing, continuous guidance was considered crucial to ensure the sustainability of integrated coconut processing ventures. This program proved that skill development in coconut processing could be a viable strategy for the economic upliftment of rural communities.